Unusual Ludwig´s angina in systemic disabled patient related with periodontal disease (Research, Society and Development, 2021)
The Ludwig's angina is an infectious process involving submandibular, sublingual, and submental spaces bilaterally. They can rapidly progress to airway obstruction and hemodynamic instability. The most common cause of Ludwig's angina is apical dental infections, specifically involving the roots of second and third mandibular molars, which are contiguous to the submandibular space. Periodontal diseases are related with bone loss around dental roots and create a situation where the inflammatory drainage tends to assume a sulcular direction. The purpose of this article is to report a clinical patient with an unusual development of a periodontic-endodontic lesion leading to Ludwig's angina in patient whit diabetics, hypertension and chronic kidney disease. Thus, we can conclude that even if it is not common reports of angina associated with periodontal diseases we must attend to patient's correct care, initiating antibiotic therapy, maintenance of the airways, removal of infectious focus and control of comorbidities diseases.